Epidemiology, Diagnosis, and Treatment of HIV-Associated Non-Hodgkin Lymphoma in Resource-Limited Settings. (26th March 2012) - Ulrickson, Matthew; Press, Oliver W.; Casper, Corey
Abstract : Lymphoma was a common complication of HIV infection in the pre-antiretroviral era, and the incidence of HIV-associated lymphoma has dropped dramatically since the introduction of combination antiretroviral therapy (cART) in resource-rich regions. Conversely, lymphoma is an increasingly common complication of HIV infection in resource-limited settings where the prevalence of HIV infection is high. Relatively little is known, however, about the true incidence and optimal treatment regimens for HIV-associated lymphoma in resource-poor regions. We review the epidemiology, diagnosis, and treatment of HIV-associated non-Hodgkin lymphoma in developing nations and highlight areas for further research that may benefit care in both settings. Examples include risk modification and dose modification of chemotherapy based on HIV risk factors, improving our understanding of the current burden of disease through national cancer registries, and developing cost-effective hematopathological diagnostic strategies to optimize care delivery and maximize use of available chemotherapy.